Juvenile ossifying fibroma accompanied with low-grade central osteosarcoma in sinonasal: a rare case report - Solichin, Muchamad Ridotu; Hakim, Fikar Arsyad; Dwianingsih, Ery Kus (Published by Universitas Gadjah Mada, 2024)
Sinonasal osteosarcoma is comparatively rare and accounts for 6.5% of all osteosarcomas. The five-year survival rate is less than 25% and may be improved to 60% when chemotherapy is initiated earlier. The diagnosis of low-grade central osteosarcoma requires a meticulous histopathological examination because histopathologically the tumor may mimic fibro-osseus neoplasm. We report a 12 y.o. male patient who complained of a lump on the face for 4 yr with symptoms of nasal discharge, congestion, epistaxis, and a feeling of fullness in the ears. Sinonasal biopsy was later performed and revealed an inverted papilloma. Two months after the biopsy procedure, mass extirpation and medial maxillectomy were performed. Histopathology examination confirms the diagnosis of ossifying fibroma accompanied by low-grade central osteosarcoma. Low-grade central osteosarcoma is an exceptionally rare variant, and the diagnosis is occasionally difficult. It can be misdiagnosed as a benign lesion, especially fibrous dysplasia or ossifying fibroma. Histomorphological, the discovery of atypical tumor cells producing osteoid matrix can be used to confirm that the lesion is a malignant lesion of low-grade central osteosarcoma. As demonstrated in our case, the tumor can consist of a trabecular and curvilinear arrangement of immature bone, at the edges of which there is an osteoblastic rimming appearance with a background of connective tissue stroma which is a histopathological feature of ossifying fibroma.